Formation of indicators for assessing the economic efficiency of innovations - Dolyna, I. V.; Pererva, P. G. (My University, 2023)
It has been proven that the effectiveness of basic research for the nearest period of time cannot, in principle, have a value expression. Economy at this stage will entail a reduction in the theoretical reserve and a decrease in the level of applied topics. This effect can be measured relative to a specific study (topic) only through peer review.
Формування показників оцінки економічної ефективності інновацій
Keywords: innovative activity; performance indicators; intellectual property; commercialization